Scoping Food Security at Barabardiya Municipality - Rawal, Sunil (Patan Pragya, 2022)
The article investigates the state of food security of Barabardiya urban municipality, Bardiya. Food security is difficult to assess, with erratic occurrence rates and patterns. Policies should address the behavioral issues that influence our dining decisions. Sociology is particularly well-suited to tackling food security since it is multidisciplinary in nature and encompasses many interdisciplinary ideas in addition to social and economic factors. The research in this study was evaluated using data gathered for my PhD dissertation. The main search engines for finding pertinent data are Google Scholars, JSTOR, Z-library, Research Gate, and the Central Bureau of Statistics of Nepal. From a total of 5981 families, 361 homes were randomly selected for thestudy.89.47 percent of the 361 respondents claimed they did not eat any less than they thought they ought to. Nearly all respondents (96.12%) responded "No," suggesting they were not required to forgo a meal. 63.43 percent of those surveyed claimed that their household never ran out of food. Nearly 93, 4% of those surveyed reported being hungry yet going without food. 96.7 percent of individuals surveyed claimed they went without food for the entire day. According to the investigation’s results, Bardiya has a decent level of food security.